Can cities become smart without being sustainable? A systematic review of the literature. (February 2019) - Yigitcanlar, Tan; Kamruzzaman, Md.; Foth, Marcus; Sabatini-Marques, Jamile; da Costa, Eduardo; Ioppolo, Giuseppe
Highlights: Explores whether smart city policy and sustainability outcomes are intertwined. Reviews the literature highlighting limitations of smart cities to achieve sustainability. Reveals that cities cannot be truly smart without being sustainable in the first place. Advocates the sustainable and knowledge-based development of smart cities. Emphasises the need for a post-anthropocentric urban turnaround for sustainability. Abstract: Smart cities are widely seen as localities that actively embrace new technologies to achieve desired urban outcomes. Despite sustainability often claimed to be a desired outcome of smart city initiatives, little evidence exists how sustainability outcomes are incorporated or achieved within the smart city initiatives. This paper aims to address the question of whether cities can become smart without actually being sustainable. The study undertakes a systematic review of the smart and sustainable cities literature. The analysis highlights an expectation in the reviewed academic literature for cities to become sustainable first in order to be considered truly smart. The results point to major challenges of smart cities in delivering sustainable outcomes: (a) Smart city policies are characterised by heavy technocentricity; (b) Smart city practices involve complexities, and; (c) Smart city notions are conceptualised in an ad-hoc manner. The findings provide evidence that the current smart city practice fails to incorporate an overarching sustainability goal that is progressive and genuine. This, then, highlights the need for a post-anthropocentric approach in practice and policymaking for the development of truly smart and sustainable cities. The findings seek to stimulate prospective research and further critical debates on this topic.